ANALISIS KELAYAKAN FINANSIAL LADA HITAM (Studi Kasus di Propinsi Lampung) - TJETJEP NURASA; ADE SUPRIATNA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
This study was implemented in 2002 and took place in Lampung Province,and then Sub-Province of North Lampung, as central production of Lampungblack pepper, was chosen as a research location. The objectives of study were:(i) to analyze the financial visibility of pepper farm, (ii) to identify the channel ofblack pepper marketing and its margin in each agent of marketing, and (iii)toanalyze the comparative and competitive advantages of black pepper. Researchused the method of structured survey. Primary data were collected from 60farmers, 15 merchants, 5 agents of processing, and exporters. While secondarydata were collected from Central Agency of Statistics, the Office of Estate Crops,and Institutions of Research related to this study. The financial visibility of pepperfarm was counted by using method of input-output analysis to get value ofBeneficial Cost Ratio (B/C Ratio), Net Present Value (NPV), and Internal Rate ofReturn (IRR). While the value of comparative and competitive advantages wereestimated by using method of Policy Analysis Matrix (PAM). Results showed that,period of pepper farm was 10 years where in the fourth year, pepper crop startedcreate production of Rp.7.682 million and earnings of Rp.4.376. In sixth year, itgave the highest production and earnings, namely Rp.9.849 million and Rp.7.816million, respectively. While in the tenth year, it reached the lower production ofRp.5.318 million and earnings of Rp.3.028 million/ha/year. At interest rate of 24percent, it took NPV of Rp.0.27 million per hectare with B/C Ratio of 1.02. At levelof input-output actual, break-even point of pepper farm reached IRR of 24,63percent. Eighty percent of farmers sold their black pepper to small collectingmerchant and the others (20%) sold to large collecting merchant. The smallcollecting merchant (90%) sold black pepper to large collecting merchant andthen large collecting merchant sold them to large merchant/exporter. The highestprofit margin successively happened at large collecting merchant (Rp.505), largemerchant/ exporter (Rp.500), and small collecting merchant (Rp.440)/kg pepperseed. The highest value of DRCR was happened in the sixth year, namely 0.22.While in fourth and eighth year, it reached DRCR of 0.32 and 0.30, respectively.At the other side, the value of competitive advantage also saw adequately, thatwas 0.41 (in fourth year), 0.20 ( in sixth year), and 0.30 (in eighth year).